2005
DOI: 10.1111/j.1365-2230.2004.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulins in psoriatic erythroderma

Abstract: The cause of psoriatic erythroderma (PE) is still unknown. Elevation of serum IgE has been reported in erythroderma, and as serum hyper-IgE is Th2 cell dominated it is of interest to investigate the serum IgE level in PE. In this study, the level of immunoglobulins in the sera of PE patients was analysed by a retrospective case-control study using psoriasis vulgaris (PV) patients as controls. The PE and PV patients were matched in a 1:3 pattern: the first three age and sex matched PV inpatients were selected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 21 publications
(51 reference statements)
4
31
2
3
Order By: Relevance
“…Moreover, we demonstrated that all types of psoriasis had significantly increased serum IgE levels compared to the controls. In agreement with our data, a case-control study showed that the mean level of serum IgE in PE patients was much higher than that in PV patients and they suggested that a shift from Th1 to Th2 occurred in PE [10]. The IgE levels were also higher in PsA patients in our study, but the difference between PsA and PV was not statistically significant.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, we demonstrated that all types of psoriasis had significantly increased serum IgE levels compared to the controls. In agreement with our data, a case-control study showed that the mean level of serum IgE in PE patients was much higher than that in PV patients and they suggested that a shift from Th1 to Th2 occurred in PE [10]. The IgE levels were also higher in PsA patients in our study, but the difference between PsA and PV was not statistically significant.…”
Section: Discussionsupporting
confidence: 82%
“…The result is consistent with some studies [7][8][9][10][11]. Yan et al demonstrated that 39% of patients with psoriasis had elevated serum IgE concentrations and they observed that lesional skin of patients with psoriasis contains more IgE+ and FceRI+ cells [20].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…psoriatic erythroderma. Li's research showed the serum IgE level was found to be elevated in 81.3% of patients with psoriatic erythroderma in comparison to 6.3% of psoriasis vulgaris patients as controls [13]. Our study shows that this phenomenon may occur in patients who suffer from mild and moderate disease and the antibody titre correlates with intensity of dermal changes (PASI scale).…”
Section: Discussionmentioning
confidence: 46%
“…Li et al [8] performed a study on serum immunoglobulins in psoriatic erythroderma. Serum IgE level was found to be elevated in psoriatic erythroderma patients than the controls.…”
Section: Prlmentioning
confidence: 99%